7 - Book Reviews: Coming to Terms with the Famine and Food Question in Ethiopia: A Review of Rahmato Dessalegn, Famine and Survival Strategies , Uppsala, The Scandinavian Institute of African Studies, 1991, 246 pages: by Nyangabyaki Bazaara - Nyangabyaki Bazaara (Africa Development, 1992)
Abstract